A study of island network performance for streaming protocols - Mohammed, Ammar Hatem (2019)
Nowadays video surveillance is a cornerstone of the security in the world. It provides real-time monitoring for alarm of the environment, for people as face recognition, for property as plate car numbers detection, and provides a recorded archive for investigation. With megapixel cameras becoming increasingly widespread, even the bandwidth exhaustion of corporate networks is becoming a real issue. In this research, study on the performance of the island network using streaming protocol of HTTP and RTSP to broadcast the IP camera when streaming executed on H264 and H.265 encoder was conducted. The research done on the real island network that build to use as test bed for the project, also used network emulator (NetEm) to inject the packet loss and delay to the island network to emulate real big network. Then the results were analysed by Wireshark packet analyser. Based on the results gained, it was found that HTTP over TCP has less packets when compared to RTSP. As a conclusion, Hypertext Transfer Protocol is a little superior and authoritative protocol to stream a video when compared to the RTSP protocol.